Psychological Features of the Development of National Musical Imagination in the Younger Generation (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article analyzes the psychological characteristics of the process of forming and developing national musical perceptions in the minds of the younger generation. The influence of national music, the aesthetic worldview and musical memory of young children, as well as the role of pedagogical approaches in this process are highlighted.